The Covid-19 Pandemic in Indonesia: Problems Identification and Solutions for Micro, Small and Medium Enterprises (MSMEs) - Rahmad Solling Hamid; Muhammad Ikbal; Muhammad Harun Ar-Rashid (Budapest International Research and Critics University, 2021)
Strategic issues regarding the development of Micro, Small, and Medium Enterprises (MSMEs) need to get significant attention from the government to develop and be more competitive with other economic actors. Various MSME development policy agendas do not have a comprehensive and implementable program to build a solid MSME sector. This study aims to identify the obstacles and solutions faced by (MSMEs) during the Covid-19 Pandemic. This research method is a qualitative method with media analysis using steps coding content using NVivo software as the analytical tool. The research findings show that development, capital, marketing, product, and technology are the main problems faced by MSMEs to survive amid the Covid-19 pandemic. MSMEs' solutions include creative economy, accessing capital, loan restructuring facility, digital marketing, digital marketing training, human resource capacity, online business, and credit facilities.